Technical and Economic Assessment of Storage Technologies for Power-Supply Grids - H. Meiwes (Acta Polytechnica, 2009)
Fluctuating power generation from renewable energies such as wind and photovoltaic are a technical challenge for grid stability. Storage systems are an option to stabilise the grid and to maximise the utilisation factors of renewable power generators. This paper analyses the state of the art of storage technologies, including a detailed life cycle cost comparison. Beside this, benefits of using storage systems in electric vehicles are analysed and quantified. A comprehensive overview of storage technologies as well as possible applications and business cases for storage systems is presented.